4y-2+y+33=7y+40-5y

Simple and best practice solution for 4y-2+y+33=7y+40-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-2+y+33=7y+40-5y equation:


4y-2+y+33=7y+40-5y

We simplify the equation to the form, which is simple to understand
4y-2+y+33=7y+40-5y

We move all terms containing y to the left and all other terms to the right.
+4y+1y-7y+5y=+40+2-33

We simplify left and right side of the equation.
+3y=+9

We divide both sides of the equation by 3 to get y.
y=3

See similar equations:

| 8x-7-3x=8 | | 2(x+4)=x-2 | | 0.9=5d+0.4 | | -5d+5=10 | | 4(3+5x)-1=51 | | 3n-4=-13 | | 4x-6x=6 | | 3(2x+1)-2(2x+1)=10 | | -6x-9x=-60 | | (1.2)(-5)= | | (-9x^2+3x-7)+(-4x^2-x)= | | 3x+4=-59 | | x^2+14x+42=0 | | 3x^2+1=2x | | 2x^2+16x=66 | | 8x=-25 | | 2z-3y-8z+1y= | | 3(x-2)-9=0 | | 2z-3y-8z-1y= | | 2-x=5 | | (5m+2n-4)-(2m-3n-7)= | | 3a+2+1= | | 2(x+7)=(2x+14) | | (4x-11)=(x+6) | | 3x-5x+17=12-(6x+3) | | x(x+1)-3(x+1)= | | 8x^2-4x+2=0 | | 9+2m=-3-4m | | x(x+3)-5(x+3)= | | 45=0.5(6+3) | | -9x=-27 | | 6(k-5)-(2k-4)=7k |

Equations solver categories